أثر قرار توزيع الأرباح في القيمة السوقية للشركات المُدرجة في سوق دمشق للأوراق المالية - عمار قصي; محمد رامي; عمر محمد ايمن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This study aims at determine the effect of dividend decision (independent variable) on the market value of listed companies in Damascus Security Exchange (dependent variable) during the period (2014-2018). To achieve this objective, the researchers compared the average of change in market value before and after the date of general assembly with the average of change in market value of the market index during the same period. The researchers used a hypothetical-deductive approach to formulate the hypotheses; and the Wilcoxon test (at 5% significance level). The study concluded that there is a significant negative effect of cash dividend decision on the market value. The distribution of bonus shares has a significant positive effect on market value. Finally, there is no significant effect of the non-dividend decision on the market value compared to the market index. يهدف هذا البحث إلى معرفة أثر قرار توزيع الأرباح كمتغير مستقل في القيمة السوقية لأسهم الشركات المدرجة في سوق دمشق للأوراق المالية كمتغير تابع خلال الفترة الممتدة 2014-2018 ولتحقيق هذا الهدف، قام الباحث بمقارنة مقدار التغير في متوسط القيمة السوقية قبل وبعد تاريخ اجتماع الهيئة العامة للشركات خلال سنوات الدراسة مع مقدار التغير في متوسط القيمة السوقية لمؤشر السوق خلال نفس الفترة للوقوف على مدى تأثر أسعار الأسهم لكل شركة حول تاريخ اجتماع الهيئة مقارنة بأداء السوق ككل وذلك اعتمادا على المدخل الاستنباطي باستخدام اختبارWilcoxon test وقد خلصت الدراسة إلى وجود تأثير سلبي معنوي عند مستوى دلالة 0.05 لتوزيع الأرباح نقدا على القيمة السوقية، وكان لتوزيع الأسهم المجانية تأثير إيجابي معنوي في القيمة السوقية عند مستوى دلالة 0.05، ولم يكن هناك تأثير ذو دلالة معنوية لقرار عدم توزيع الأرباح على القيمة السوقية مقارنة بمؤشر السوق.